(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The purpose was to investigate the effectiveness of a group E-therapy program on improving children’s social skills with ASD. Participants were (16) children between the ages of Six and eleventh. A pre-post design was used to examine the effectiveness of group therapy on developing social skills in children with Autism. Stone’s social skills Scale was administered to assess children’s social skills with autism spectrum disorder as a pre-post-test. The group therapy strategies were performed on the experimental group by their actual teacher during an exact 8-week lesson period with 50-minute sessions three times per week. The Z-value results for the differences in the mean post-test scores between the experimental and control groups in social skills. The table shows that the value of (Z) ranged between (2.809 - 3.354). These values are significant at (0.01) level in favor of the experimental group. The value of (Z) in Table 2 ranged between (2.617 - 2.711), which are significant values at the level (0.01). This indicates that group therapy had a positive effect on social skills in children with ASD.